Understanding undergraduates' problems from determinants of Facebook continuance intention. Issue 9 (1st September 2016) - Lin, Kan-Min
ABSTRACT: As social networks' popularity has increased, so have the attendant problems. The purpose of this study is to identify the important problems by exploring the determinants of Facebook continuance intention from a negative perspective. A questionnaire survey and interview method is used to provide a deep understanding of both the problems and their causes. The research hypotheses are empirically evaluated using the responses from a field survey of 555 undergraduates. The results indicate that previous usage behaviour is the most important determinate of continuance intention. There is a positive causal relationship between perceived privacy self-protection and usage behaviour. In addition to a common privacy issue, this study discovers some problems such as underestimating the potential risks, having misconceptions and lacking legal and information security knowledge. Moreover, this study presents a diagnostic system that administrators can use to detect students' key problems and understand the reasons behind students' behaviour.